An international epidemiological analysis of young patients with non-small cell lung cancer (AduJov-CLICaP) (2020)
Background A proportion of patients with NSCLC is diagnosed at 40 years or younger. These patients tend to be never-smokers, usually present with stage IV adenocarcinoma, and have somatic genomic alterations. Few studies have documented and analyzed epidemiological characteristics of this population. Materials and methods We performed an international epidemiological analysis of 389 young patients with NSCLC. Data was collected from centers participating in the Latin American Consortium for Lung Cancer Research (AduJov-CLICaP). Patients were identified and data was retrospectively collected from different Latin American countries and Canada (Argentina = 6, Canada = 19, Colombia = 29, Costa Rica = 9, Mexico = 219, Nicaragua = 2, Panama = 19, Perú = 76 and Venezuela = 10). The period of study was from 2012 to 2017. Inclusion criteria were: age 40 years or less and a histologically confirmed NSCLC. Clinical data was obtained, and EGFR mutation status and EML4-ALK translocation were collected. Results NSCLC patients aged 40 years or less accounted for approximately 4% of the total NSCLC population. Female patients accounted for 54.5%, while median age was of 37 years. Adenocarcinoma accounted for 86.1% (n = 335/389), 72.5% (n = 282/389; unknown = 5) of patients were non-smokers, and 90.3% (n = 351/389) had stage IV disease. Site of metastasis was obtained from 260/351 (unknown = 91) stage IV patients (lung metastasis = 40.0%, CNS metastasis = 35.7%, and bone metastasis = 31.5%). OS for the total population was 17.3 months (95%CI = 13.9-20.7). OS for EGFRm(+) = 31.4 months (95%CI = 11.6-51.3), EGFRm(−) = 14.5 months (95%CI = 11.0–17.9) (p = 0.005). OS for alk(+) = 9.8 months (95%CI = 3.1-16.5) and alk(−) = 5.6months (95%CI = 3.9–7.3) (p = 0.315). Conclusions Patients aged 40 years or less account for a small but important proportion of NSCLC cases. Younger patients may have different characteristics compared to the older population. EGFRm and EML4-alk translocation frequency is higher than that of the general population.